Clinical practice in secondary prophylaxis and management of febrile neutropenia in Poland: results of the febrile neutropenia awareness project - Wojtukiewicz, Marek; Chmielowska, Ewa; Filipczyk-Cisarż, Emilia; Krzemieniecki, Krzysztof; Leśniewski-Kmak, Krzysztof; Litwiniuk, Maria M.; Wieruszewska-Kowalczyk, Karolina; Kosno-Kruszewska, Elżbieta (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study : This paper presents the second part of the GoPractice project involving oncologists from seven Polish provinces. The aim of this part of the project was to assess the knowledge of oncologists on indications for granulocyte colony-stimulating factor (G-CSF) secondary prophylaxis (SP) of febrile neutropenia (FN) and FN management based on current therapeutic guidelines (Polish Society of Clinical Oncology [PTOK] and European Organisation for Research and Treatment of Cancer [EORTC]). Material and methods: The project involved 169 oncologists from 7 regions working in large specialist oncological centers, university hospitals, regional and city hospitals, specialist outpatient clinics and oncological wards in small, local hospitals. The participants completed a questionnaire based on 7 prepared clinical cases of patients with different tumor types and patient characteristics, receiving chemotherapy (CT) with different levels of FN risk. Participants answered questions related to FN risk assessment and G-CSF use as secondary prophylaxis (SP) and for the management of FN. After completing the questionnaire, the participants proceeded to an educational module in which they were provided with an analysis of correct diagnostic and therapeutic procedures according to the PTOK and EORTC guidelines. Results and Conclusions : Indications for G-CSF SP were generally well recognized: in nearly 90% of responses, oncologists assessed correctly indications/lack of indications for secondary prophylaxis, in accordance with guideline recommendations and Experts’ opinion. However, the use of daily G-CSFs was often recommended by the study participants for the management of FN. This clinical practice is contradictory to PTOK and EORTC recommendations and may unnecessarily increase treatment costs. Changing this clinical approach may be achieved through regular training to improve guideline adherence.